Solar energy for socio-economic wellbeing in urban areas, Malaysia - Rashidah Zainal Alam,; Md. Anowar Hossain Bhuiyan,; Chamhuri Siwar,; Norasikin Ahmad Ludin, (Institut Alam dan Tamadun Melayu, Universiti Kebangsaan Malaysia, 2016)
The dependency of energy in terms of electricity becomes one of the promising needed sources for people in urban areas in Malaysia. Renewable energy could become one of the alternative sources for people in urban areas to gain environmental, economic and social wellbeing. Among the alternative sources, solar energy is one of the potential energy sources in tropical countries particularly in Malaysia for sustainable urban development. This study attempts to analyze the benefits and advantages related to solar energy for sustainable energy use and urban development. The study is using secondary sources of data such as policies, regulations and research reports from relevant ministries and agencies to attain the objectives. As began under Fifth Fuel Policy in 8th Malaysia Plan, Malaysia has taken initiatives for decreasing energy dependency on oil in a way to address the global concern on climate change by introduced solar as one of the alternative renewable energy in the energy supply mix for sustainable development. The study shows solar energy becomes one of the promising alternative energy sources for Malaysia in urban areas. Finally, solar energy has increased socio-economic wellbeing and develops green potential in energy sector of Malaysia by preserving environment as well as reducing carbon emission.